Wise and Appropriate Antibiotic Usage Education to Prevent Resistance Risk in Kenoyojayan Ambal Village, Kebumen: Edukasi Penggunaan Antibiotik yang Bijak dan Tepat untuk Mencegah Resiko Resistensi di desa Kenoyojayan Ambal, Kebumen - Ayuningtyas, Ervina; Ainni, Ayu Nissa; Rahayu, Titi Puji; Sodik, Anwar (Prosiding University Research Colloquium, 2023)
Antibiotic resistance is a critical health issue that must be addressed. Antibiotic resistance occurs when antibiotics are no longer effective in killing bacteria. High levels of antibiotic resistance can lead to various health problems, including an increase in disease incidence and mortality rates, as well as higher treatment costs and therapy failures. Inappropriate antibiotic use is often attributed to the lack of public knowledge about how to use antibiotics wisely and correctly. Therefore, the objective of this activity is to provide an understanding of the prudent use of antibiotics to prevent drug resistance. This community engagement is carried out through the delivery of materials and discussions with the PKK mothers as the audience. Based on the results obtained from the community engagement, there is an improvement in the knowledge of PKK mothers in the Kenoyojayan Village regarding the wise use of antibiotics. In conclusion, education and outreach can enhance the knowledge of PKK mothers about the prudent use of antibiotics.